Chemical Profile and Skin-Beneficial Activities of the Petal Extracts of Paeonia tenuifolia L. from Serbia - Natalija Čutović; Tatjana Marković; Marina Kostić; Uroš Gašić; Željana Prijić; Xiuxia Ren; Milan Lukić; Branko Bugarski (Pharmaceuticals, 2022)
Without being aware of its chemical makeup, many ancient societies have used Steppe peony in their traditional medicine. Given that modern phytopreparation intended for use on human skin requires, above all, knowledge of its chemical composition, the goal of this study was to make a screening of the composition of aqueous and methanolic extracts of the petals of P. tenuifolia L. and to examine them for various skin-beneficial properties. The extracts were prepared by maceration, ultrasound-assisted, and microwave-assisted extraction procedures. The chemical profiling was conducted by the use of UHPLC-LTQ-OrbiTrap MS and UHPLC/MS, and spectrophotometric methods for the determination of total polyphenol and total flavonoid contents. The biological activities entailed antioxidant ABTS, DPPH, CUPRAC (Cupric Ion Reducing Antioxidant Capacity), and FRAP (Ferric Reducing Antioxidant Power) assays, antimicrobial (antibacterial and antifungal) and antibiofilm activities, cytotoxicity, wound healing potential, as well as the adhesion and invasion of Staphylococcus lugdunensis. The results showed that the petals are rich in phenolic acids and flavonoids, which are commonly associated with numerous biological activities. The aqueous extracts were more efficient in the majority of the bioactivity assays then the methanolic ones, whereas the optimal extraction method varied between the assays. This study is the first step towards the safe use of the aqueous extracts of P. tenuifolia petals for therapeutic skin treatments.